Zeolite membrane with sub-nanofluidic channels for superior blue energy harvesting - Ruicong Wei; Xiaowei Liu; Li Cao; Cailing Chen; I-Chun Chen; Zhen Li; Jun Miao; Zhiping Lai (Nature Communications)
Abstract Blue energy, a clean energy source derived from salinity gradients, has recently drawn increased research attention. It can be harvested using charged membranes, typically composed of amorphous materials that suffer from low power density due to their disordered structure and low charge density. Crystalline materials, with inherently ordered porous structures, offer a promising alternative for overcoming these limitations. Zeolite, a crystalline material with ordered sub-nanofluidic channels and tunable charge density, is particularly well-suited for this purpose. Here, we demonstrate that NaX zeolite functions as a high-performance membrane for blue energy generation. The NaX zeolite membrane achieves a power density of 21.27 W m⁻² under a 50-fold NaCl concentration gradient, exceeding the performance of state-of-the-art membranes under similar conditions. When tested under practical scenarios, it yields power densities of 29.1 W m⁻², 81.0 W m⁻², and 380.1 W m⁻² in the Red Sea/River, Dead Sea/River, and Qinghai Brine/River configurations, respectively. Notably, the membrane operates effectively in high alkaline conditions (~0.5 M NaOH) and selectively separates CO₃²⁻ from OH⁻ ions with a selectivity of 25. These results underscore zeolite membranes’ potential for blue energy, opening further opportunities in this field.